Gamification in Genetics: Effects of Gamified Instructional Materials on the STEM Students’ Intrinsic Motivation - Funa, A. A.; Gabay, R. A. E.; Ricafort, J. D. (Jurnal Pendidikan IPA Indonesia, 2021)
Gamification in education offers an innovative way of learning. However, some studies claim that, while it helps raise students' motivation, the kind of motivation is extrinsic and, so, intrinsic motivation declines with time. The researchers used the descriptive research design to describe the STEM students’ intrinsic motivation along with the utilization of game elements in teaching genetics through a learning management system. The researchers collected quantitative data using the Intrinsic Motivation Inventory, which were analyzed through descriptive statistics and complemented with qualitative data from the students' journals and interviews. Overall, the students agreed (M = 5.38, SD = 1.20) that gamification, despite being characterized as extrinsically motivating, had intrinsically motivated them. Its proper implementation helps students adapt to and overcome unfavorable behaviors towards competitiveness and emphasizes the role of teachers in facilitating learning. Time constraints, peer pressure, and distractions were noted; hence, more research is needed to address these challenges and determine the long-term effects of gamification.